Probing the structural basis of RecQ helicase function. - Vindigni, A; Marino, F; Gileadi, O (2010)
RecQ helicases are a ubiquitous family of DNA unwinding enzymes required to preserve genome integrity, thus preventing premature aging and cancer formation. The five human representatives of this family play non-redundant roles in the suppression of genome instability using a combination of enzymatic activities that specifically characterize each member of the family. These enzymes are in fact not only able to catalyze the transient opening of DNA duplexes, as any other conventional helicase, but can also promote annealing of complementary strands, branch migration of Holliday junctions and, in some cases, excision of ssDNA tails. Remarkably, the balance between these different activities seems to be regulated by protein oligomerization. This review illustrates the recent progress made in the definition of the structural determinants that control the different enzymatic activities of RecQ helicases and speculates on the possible mechanisms that RecQ proteins might use to promote their multiple functions.